Exegesis in the Making Postcolonialism and New Testament Studies - Runesson, Anna (Leiden BRILL, 2010)
Known for its fresh approaches as well as for its complex theoretical foundations, postcolonialstudies is one of the most dynamic contributions to the field of biblical studies today. The presentbook is a pedagogically structured introduction to this emerging field for both scholar and student.
Intro -- Contents -- List of Illustrations -- Preface -- Acknowledgements -- Abbreviations -- Chapter One Introduction -- Part One The Theoretical Location and Contribution of Postcolonial New Testament Studies -- Chapter Two Introduction -- 2.1 Procedure -- 2.2 Postcolonial Studies: Some Initial Remarks -- Chapter Three The Theoretical Location of Postcolonial Studies -- 3.1 The Postcolonial Phenomenon: A Presentation and a Definition -- 3.1.1 Excursus: Who is a Postcolonial Scholar? -- 3.2 Perspectives and Methods -- 3.2.1 Episteme: What is Reality? -- 3.2.2 Deconstruction-a Theory and a Method -- 3.3 Postcolonial Studies and New Testament Exegesis -- 3.4 Summary -- Chapter Four Deconstructing Western Biblical Studies -- 4.1 Introduction -- 4.2 Exegesis in a Nutshell: A Short Presentation of its History -- 4.2.1 Defining Exegesis -- 4.2.2 The Historical Critical Discourse -- 4.2.3 Summary -- 4.3 Postcolonial Critique of Traditional Historical Critical Discourse -- 4.3.1 General Critique of Historical Critical Discourse -- 4.3.1.1 Positivism and 'Objectivism' -- 4.3.1.2 The Nature and Intention of the Biblical Text -- 4.3.2 Specific Critique of Historical Critical Discourse -- 4.3.2.1 Orientalism and the Portrayal of 'the Other' -- 4.3.2.2 Hegemony and Truth Claims -- 4.3.2.3 Relevance as a Critical Problem -- 4.3.3 Kwok and the Quest for the Historical Jesus: A Test Case -- 4.3 Summary -- Chapter Five Constructing Postcolonial Biblical Analysis -- 5.1 Redefining Exegesis: Introducing Postcolonial Approaches -- 5.2 Category One: Postcolonial Analysis within the Historical Critical Paradigm -- 5.2.1 Tracing Colonial Elements and Abuses in New Testament Texts -- 5.2.2 Mapping Colonial Spread of Western Biblical Criticism -- 5.2.3 Translating the Bible in an Indian Context -- 5.2.4 Inter-Textual Comparisons.
Description based on publisher supplied metadata and other sources
Keywords: Bible ; N.T ; Postcolonial criticism; Electronic books